Les contes francophones comme déclencheurs d'activités visant a développer les compétences langagieres - Žugelj, Nataša (Vestnik za tuje jezike, 2015)
Traditional folktales as an authentic document belong to a literary genre which can be of great use in enhancing foreign language learning. When accompanied by diverse and fun activities, they can convert a foreign language learning into a very positive experience for different age groups. Folktales with language exercises for developing different language skills can be a great source for language analysis, vocabulary building and better expression in a foreign language. Its restricted length and its identifiable content make folktales user-friendly for teaching.
Keywords: francoščina; French; pripovedke; pravljice; jezikovne spretnosti; slušno razumevanje; bralno razumevanje; govorno sporočanje; pisno sporočanje; didactic method; didaktika